Strategies and technologies for developing online computer labs for technology-based courses - Chao, Lee. (Hershey : IGI Publishing, 2008)
"This book discusses design strategies, implementation difficulties, and the effectiveness of online labs. It provides scholars, researchers, and practitioners support for lab-based e-learning, gives guidance on the selection of technologies for various projects, and illustrates Web-based teaching with case studies"--Provided by publisher
Includes bibliographical references and index.
Keywords: Computer networks -- design and construction; Instructional materials centers -- design and construction; Schools -- computer networks -- design and construction; Educational technology; Web-based instruction